MODEL RIGHT ISSUES DAN RASIO SOLVABILITAS MENINGKATKAN PENILAIAN HARGA SAHAM PADA PASAR MODAL INDONESIA - Rahim, Eka; Nurita, Endang; Akbar, Akhmad (Yayasan Education and Social Center, 2025)
This research aims to determine whether or not there is an influence of Right Issues and debt to equity ratio on share prices of issuers listed on Index 80 for the 2015-2022 period. The data used in this research is secondary data, namely issuers that carry out limited public offerings (PUT) with the HMETD system registered in Index80 for the 2015-2022 period. The method used in this research is a quantitative method, with data analysis methods namely descriptive analysis, data normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression, R Square coefficient of determination analysis test, t test, and F test. Variables in this research are HMETD (X1) and Debt to Equity Ratio (X2) to Share Price (Y). Based on the results of the first hypothesis test, HMETD has a significant positive influence on share prices (tcount > ttable) and significance value (). The results of the second hypothesis, DER has no influence on stock prices (tcount > ttable) and significance value (). The results of the third hypothesis, HMETD and DER have a significant positive influence on stock prices (Fcount > Ftable) and significance value ().Keywords: HMETD, Debt to Equity Ratio, Share Price.